2013
DOI: 10.1007/s10792-013-9827-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased central corneal thickness in ankylosing spondylitis

Abstract: Central corneal thickness and dry eye tests were evaluated in a study population consisting of 68 ankylosing spondylitis patients diagnosed according to the modified New York criteria, and 61 age-matched controls without ankylosing spondylitis. A full ophthalmological evaluation was performed on each subject. All subjects were screened for age, gender, HLA-B27, tear break-up time test, Schirmer test, and duration of disease. Central corneal thickness was measured under topical anesthesia with an ultrasonic pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Ortak et al also found thinner corneas and lower dry eye tests in a group of 68 AS patients. Consequently, they suggested careful attention in surgical interventions such as photorefractive keratectomy and laser in situ keratomileuses in AS patients 39 . Despite the dysfunctional dry eye tests found in these studies, the authors did not determine the DED severity level.…”
Section: Discussionmentioning
confidence: 99%
“…Ortak et al also found thinner corneas and lower dry eye tests in a group of 68 AS patients. Consequently, they suggested careful attention in surgical interventions such as photorefractive keratectomy and laser in situ keratomileuses in AS patients 39 . Despite the dysfunctional dry eye tests found in these studies, the authors did not determine the DED severity level.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have investigated the corneal biomechanical properties, such as CCT and ORA parameters in CVD. [7][8][9][10][11][12] Prata et al have demonstrated abnormal corneal biomechanics in patients with rheumatoid arthritis (lower corneal hysteresis and IOP values than healthy controls). 8 Similarly, Yazici et al 9 have reported that patients with systemic lupus erythematosus present with lower corneal hysteresis, lower corneal resistance factor (CRF), and Goldmann-related IOP values compared with age-matched controls.…”
Section: Corneal Biomechanical Properties In Systemic Inflammatory DImentioning
confidence: 99%
“…7 Recently, a study also found a significant lower CCT in patients with another CVD-ankylosing spondylitis -when compared with aged-matched controls. 12 CCT in scleroderma has been subject to debate because of conflicting reports. Although a study conducted by Serup et al 31 has found significantly increased CCT in scleroderma, recent studies have failed to confirm this finding.…”
Section: Corneal Biomechanical Properties In Systemic Inflammatory DImentioning
confidence: 99%
See 1 more Smart Citation
“…27 In their study on patients with ankylosing spondylitis (AS), Ortak et al reported thinning in CT in patients with AS compared with the control group. 28 Czompa et al compared the CT of a total of 66 inflammatory bowel disease patients (30 patients with Crohn's disease and 36 with ulcerative colitis) with the control group and found a significant reduction in CT in patients with inflammatory bowel diseases. 29 Gökmen et al found that the CT was thinner in patients with rheumatoid arthritis (RA), but this difference was not statistically significant.…”
mentioning
confidence: 99%